A longitudinal study of normal fetal femur volume. (23rd August 2013) - Ioannou, Christos; Sarris, Ippokratis; Napolitano, Raffaele; Ohuma, Eric; Javaid, M. Kassim; Papageorghiou, Aris T.
ABSTRACT: Objective: Fetal femur volume (FV) is a useful marker of skeletal growth. Our objective was to create a normal FV chart in a cohort of healthy pregnant women and to assess FV repeatability. Method: The method used was a prospective, observational study using 3D ultrasound. Low‐risk pregnant women underwent serial scans from 14 to 42 weeks. Strict inclusion and exclusion criteria were used in order to remove pathological conditions. Pregnancies were dated by last menstrual period and confirmed by crown‐rump length. FV was measured using three linear measurements and a volume equation. Data were analyzed using multilevel modeling. Repeatability was assessed using within‐subject coefficients of variation (CV), intraclass correlation coefficients (ICC), and Bland–Altman plots. Results: A total of 180 women underwent 868 scans, a median of five scans per participant. Median and centile values were presented in the form of curves, regression equations, and table of values per completed week. Intra‐observer CV and ICC were 10.5% and 0.977, respectively; interobserver CV and ICC were 16.8% and 0.923. Conclusion: This normal FV chart can be used as a prescriptive standard in order to assess fetal skeletal growth. Measurement repeatability is satisfactory for clinical use, but FV has a larger random error than commonly seen with standard 2D biometry. © 2013 John Wiley & Sons, Ltd. Abstract : What's already known about this topic? A validated method for femur volume measurement on 3D ultrasound uses three linear measurements and a volume equation. Fetal femur volume is correlated with maternal vitamin D concentration. What does this study add? A gestational femur volume chart is presented using serial ultrasound scans in healthy UK pregnancies. Measurement method repeatability is reported.